(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, it is possible to analyze and discuss the integration of the teaching process with information and communication technologies, important priority tasks and their solution in general education schools and professional education. By applying advanced pedagogical and information technologies to the teaching process of technological science on the basis of an integrative approach, the formation of basic and scientific competences of students serves to find a positive solution to the current problem. Professional maturity is an important period of human ontogeny, starting with professional development and development ideas (14-17 years old) and ending professional activity (55-60 years old). The formation and development of a creative person is carried out depending on the mutual compatibility of changes in his inner and outer world, socio-economic conditions and human ontogeny - from birth to the end of his life, the content of activity that requires continuity and succession. It is important to use different tools and methods in teaching. This includes both teaching aids and technology tools. Although they are different, they also have things in common. It’s important to learn about technology in school, figure out the best ways to use it, and decide what works best for them. It is appropriate to consider the formation of a creative person as the development of a person in terms of creative activities performed in a mutually compatible manner and creation of creative products.